If it's not what You are looking for type in the equation solver your own equation and let us solve it.
17=-d+13
We simplify the equation to the form, which is simple to understand
17=-d+13
We move all terms containing d to the left and all other terms to the right.
+1d=+13-17
We simplify left and right side of the equation.
+1d=-4
We divide both sides of the equation by 01 to get d.
d=-4
| -4*-4*-4*-4=x | | c+7=12 | | 4x+1=6x+3 | | 3(-4w)-6w=9 | | w^2-4w=16+2w | | a-1=4 | | 7(x+2)-9=5 | | -1/3(3x+9)-10x=-2x+4 | | 35*x=7 | | 13x+14=3x+314 | | 65+30k=50k+85 | | 2(x+4)=2(x-4)+4 | | -11(1+5x-2)=-3(12b-9) | | y=.5*.8+2 | | 102-7x=29x+18 | | 3(x-6)=2(x-4) | | -4(x-3)-3=9 | | n+5=27 | | u/3=9 | | -2y+4=-2(3y+6) | | 8-9x=32-30x | | 66-7x=2x+18 | | 2a-10=12 | | .5x+2=-2x+4 | | 12.7-18.5+15+6.3-1+28.5= | | 3x-17+5x=7x+10 | | 12-9x=132-30x | | 15.8=16+0.2n | | 0.7x-3.1=0.4 | | 5w=8 | | 5(2c-3)=4c+9 | | -11(1+5b)=-3(12b-9) |